2014
DOI: 10.1016/j.autrev.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22: A likely target for treatment of autoimmune diseases

Abstract: Interleukin -22 (IL-22) is a member of IL-10 family cytokines that is produced by many different types of lymphocytes including both those of the innate and adaptive immune system. This includes activated T cells, most notably Th17 and Th22 cells, and NK cells, γδ T cells, LTi cells and LTi-like cells. IL-22 mediates its effects via the IL-22-IL-22R complex and subsequent Janus Kinase-signal transduces and activators transcription (JAK-STAT) signaling pathway. Recently accumulated evidence has indicated that I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 51 publications
0
78
0
Order By: Relevance
“…However, recent an experimental study has been shown that synovial inflammation was not affected in IL-22-/-mice and this study concludes that the local IL-22 produced by adaptive or innate immune cell have no direct contribution to the induction of T cell-mediated synovial inflammation 29 . Many studies suggest that the possible explanation for these differences is depending on different phases of the disease development 29,30,41 .…”
Section: Resultsmentioning
confidence: 99%
“…However, recent an experimental study has been shown that synovial inflammation was not affected in IL-22-/-mice and this study concludes that the local IL-22 produced by adaptive or innate immune cell have no direct contribution to the induction of T cell-mediated synovial inflammation 29 . Many studies suggest that the possible explanation for these differences is depending on different phases of the disease development 29,30,41 .…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of IL-22 were found to be associated with lupus erythematosus (Zhao et al, 2013b), Sjogren's syndrome (Ciccia et al, 2012), Behcet's disease (Cai et al, 2013), asthma (Pennino et al, 2013;Manni et al, 2014), atopic dermatitis (Nograles et al, 2009), multiple sclerosis (Beyeen et al, 2010), psoriasis (Ouyang, 2010;Hao, 2013), inflammatory bowel disease (ibd) (Seiderer and Brand, 2009;Ouyang, 2010), and rheumatoid arthritis (da Rocha, 2012;Xie et al, 2012). It is interesting, however, that multiple experiments on animal models showed that IL-22 may exert either a pathogenic impact or a protective impact on the above-mentioned diseases (Yang and Zheng, 2014). In particular, two different groups independently observed that IL-22 is a survival factor for hepatocytes during acute liver inflammation (Radaeva et al, 2004;Zenewicz et al, 2007).…”
Section: Overviewmentioning
confidence: 94%
“…Interleukin-22 functions in synergy with for example IL-17 but also with TNF-α and IFN-γ [24] . T-helper 22 cells differentiate in response to TNF-α and IL-6 [23] and effects via the IL-22-IL22R complex [25] . These Th22 cells are suggested to play for example an important role in autoimmune diseases like graft versus host disease, rheumatoid arthritis, hepatitis and psoriasis [25] as well as in allergy and epidermial immunity and remodeling [26] .…”
Section: T-helper 2 Cells Require the Transcription Factors Stat6mentioning
confidence: 99%